Implementation of Income and Expense Recognition at AHASS Jaya Servis - Maisur, Hardian (Nexus Synergy: A Business Perspective, 2023)
The problem factor that the author examines is regarding the implementation of income and expense recognition at AHASS Jaya Servis. The purpose of this research was to determine whether the recognition of income and expenses applied by AHASS Jaya Servis applies accounting standards or not. The data analysis technique used is descriptive qualitative which provides an overview of the research object based on data in the field, namely primary data resulting from interviews and secondary data resulting from income and expense recording documents at AHASS Jaya Servis. The results of this research indicate that AHASS Jaya Servis at the time the transaction occurred had not fully implemented the recognition of income and expenses in accordance with the Statement of Financial Accounting Standards (PSAK 23). They record income in the daily income report and expenses in the daily expense list.